ICAR-IIOR sunflower: an android mobile app for knowledge dissemination: ICAR-IIOR sunflower: an android mobile app for knowledge dissemination - P MADHURI; H P MEENA; M SUJATHA; S N SUDHAKARA BABU; R D PRASAD (Journal of Oilseeds Research, 2023)
India has become the fastest growing mobile market in recent years. In India, there are enormous opportunities for utilizing the smart phones as a part of agribusiness improvement. Usage of smart phones is exponentially increasing in rural areas hence, providing information to large number of farmers. In this context ICAR-IIOR-SUNFLOWER, mobile app was developed by ICAR-IIOR to provide entire package of practices required for sunflower cultivation. The App supports English language and available on Google play store. Features include offline and online mode and offer valuable information to the extension workers, farmers, sunflower researchers and other stakeholders.